2019
DOI: 10.1073/pnas.1820238116
|View full text |Cite
|
Sign up to set email alerts
|

Model-free and model-based learning processes in the updating of explicit and implicit evaluations

Abstract: Evaluating stimuli along a good-bad dimension is a fundamental computation performed by the human mind. In recent decades, research has documented dissociations and associations between explicit (i.e., self-reported) and implicit (i.e., indirectly measured) forms of evaluations. However, it is unclear whether such dissociations arise from relatively more superficial differences in measurement techniques or from deeper differences in the processes by which explicit and implicit evaluations are acquired and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 45 publications
4
29
0
Order By: Relevance
“…Moreover, at least under some conditions, implicit beliefs seem to be more closely related to explicit attitudes than they are to explicit beliefs (42). Finally, a recent investigation using a reinforcement learning perspective has found that whereas implicit attitudes track a history of personally experienced rewards and punishments, explicit attitudes also reflect additional information about the structure of the environment (43). However, it should be noted that most of these results have been obtained using implicit measures of attitude and, as such, may not readily generalize to implicit measures of beliefs.…”
mentioning
confidence: 95%
“…Moreover, at least under some conditions, implicit beliefs seem to be more closely related to explicit attitudes than they are to explicit beliefs (42). Finally, a recent investigation using a reinforcement learning perspective has found that whereas implicit attitudes track a history of personally experienced rewards and punishments, explicit attitudes also reflect additional information about the structure of the environment (43). However, it should be noted that most of these results have been obtained using implicit measures of attitude and, as such, may not readily generalize to implicit measures of beliefs.…”
mentioning
confidence: 95%
“…However, rather than 16 preplay immediately prior to choice, we found evidence of on-task replay following feedback 17 alone, suggesting a third potential factor impacting on the timing and content of replaythe 18 need to minimize memory load by embedding new information in ones' policies as soon as it 19 is received. 20 Critically, the timing and content of replay differed across individuals in a manner that links 21 with their dominant mode of planning. More model-based subjects tended to replay 22 trajectories during learning, predominantly reflecting choices they were likely to reconsider.…”
mentioning
confidence: 99%
“…18 Subjects were first told explicitly how many reward points were associated with each of the 19 eight images. Subjects were then trained on these image-reward associations until they 20 reliably chose the more rewarding image of any presented pair (see Image-reward training). 21 Next, the rules of the state-space task were explained (see State-space task), and multiple- 22 choice questions were used to ensure that subjects understood these instructions.…”
mentioning
confidence: 99%
See 2 more Smart Citations